2015
DOI: 10.1021/acs.jpcc.5b01598
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Electronic Properties in Laterally and Commensurately Repeating Graphene and Boron Nitride Composite Nanostructures

Abstract: Graphene and hexagonal boron nitride (h-BN) nanoribbons of diverse widths and edge geometries are laterally repeated to form commensurate, single-layer, hybrid honeycomb structures. The resulting composite materials appear as continuous, one atom thick stripes of graphene and BN having the average mechanical properties of constituent structures. However, depending on the widths of constituent stripes they can be metal or semiconductor with band gaps in the energy range of the visible light. These two-dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 72 publications
0
13
0
Order By: Relevance
“…[134][135][136] Composite structures made of lateral and vertical junctions of 2D SL structures like Graphene/BN or MoS 2 / WS 2 that have been previously treated both theoretically and experimentally, heralded great potential for new generation artificial structures with promising applications. 20,[137][138][139][140][141] Motivated with the synthesis of very thin h-GaN and h-AlN, Onen et al 35 recently studied the composite structures of their single-layers. They showed that stable, in-plane composite materials, (GaN) p /(AlN) q can be constructed of periodically repeating stripes of GaN and AlN continuously (or commensurately) joined along their zigzag (Z) edges.…”
Section: Composite Structures Of Gan/alnmentioning
confidence: 99%
“…[134][135][136] Composite structures made of lateral and vertical junctions of 2D SL structures like Graphene/BN or MoS 2 / WS 2 that have been previously treated both theoretically and experimentally, heralded great potential for new generation artificial structures with promising applications. 20,[137][138][139][140][141] Motivated with the synthesis of very thin h-GaN and h-AlN, Onen et al 35 recently studied the composite structures of their single-layers. They showed that stable, in-plane composite materials, (GaN) p /(AlN) q can be constructed of periodically repeating stripes of GaN and AlN continuously (or commensurately) joined along their zigzag (Z) edges.…”
Section: Composite Structures Of Gan/alnmentioning
confidence: 99%
“…Since both 2D constituents have been synthesized already [17], earlier growth studies [14,18,19] and present theoretical analysis of energetics and stability let us expect that these SL composite structures with sharp boundaries can readily be produced [20][21][22][23][24] and remain stable in diverse applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recently in‐plane heterostructures of graphene and hexagonal boron nitride (h‐BN) have been investigated as an alternative monolayer semiconductor . It has been demonstrated in both theory and experiments that a bandgap can be introduced to graphene by doping with small domains of h‐BN. Furthermore, the bandgap can be tuned according to the relative concentrations of carbon and h‐BN without significantly hindering the carrier mobility .…”
mentioning
confidence: 99%